Comparison of skin fold thickness, waist circumference, waist hip ratio and BMI in predicting body fat percentage - Wijetunga, W.M.U.A.; Tilakaratne, T.A.D.; Wijesundara, W.R.U.A.S.; Subasinghe, S.; Katulanda, P. (My University, 2012)
Non communicable diseases have reached epidemic proportions all over the world. Body fat percentage (BFP) is a risk factor for many non communicable diseases including diabetes, hypertension and cardiovascular disease. Bio impedance analysis (BIA) provides an accurate way of measuring BFP but it is associated with a high initial cost. If anthropometric indices are found to be predictive of BFP, they can be used for clinical decision making with less cost.